Lettuce Cultivars for Insect Resistance in Southern Florida - Huangjun Lu; Alan L. Wright; David Sui (EDIS)
Florida’s subtropical climate facilitates lettuce production from fall through spring, but the warm, moist conditions are also favorable for insect proliferation and damage. Information about current cultivar response to common insect pests in Florida is limited, so UF/IFAS researchers conducted a study to evaluate cultivar response to insect infestation under field conditions and to identify resistance useful for integrated pest management. This 4-page fact sheet was written by Huangjun Lu, Alan L. Wright, and David Sui, and published by the UF Department of Horticultural Sciences, February 2012.